An Empirical Study of the Interest Rate Sensitivity of Commercial Bank Returns: A Multi-Index Approach - Lynge, Morgan J.; Zumwalt, J. Kenton (Journal of Financial and Quantitative Analysis, 1980)
Morgan J. Lynge, Jr., J. Kenton Zumwalt, An Empirical Study of the Interest Rate Sensitivity of Commercial Bank Returns: A Multi-Index Approach, The Journal of Financial and Quantitative Analysis, Vol. 15, No. 3 (Sep., 1980), pp. 731-742